"Sua fedlisima molge insino ala morte". Le lettere di Aurora Formentini a suo marito Ádám Batthyány - Antal, Beatrix (Verbum – Analecta Neolatina, 2003)
The paper deals with the letters written by Aurora Formentini to his husband, Ádám Batthyány in the 1630s. The documents, which are of rather low historical interest, may be analysed in respect to their language. Nobody knows what the mother tongue of the Countess in fact was. What is known is that she was born in Gorizia (Friuli), was educated in Vienna and married in Hungary. Although she was educated at the emperor’s court, her language use is far from any standard grammatical canon.